The Role of First-Time Maternal Pregnancy in Neonatal Low Birth Weight: Evidence from RSUD Toto Kabila’s NICU - NauE, Ferawaty; Ibrahim, Sri Andriani; Mohammad, Rini Wahyuni (PT. Nursing Genius Care, 2025)
Background: Based on data from the Gorontalo Provincial Health Office in 2023, the number of LBW babies was 1,285 out of 18,724 births. LBW is caused by several factors, including the mother's age during pregnancy, primigravida status, the mother's gestational age at delivery, anemia in pregnant women, intrauterine growth restriction, and the number of antenatal care (ANC) visits. Among these causal factors, the incidence of LBW is more likely to occur in first pregnancies or primigravida cases.. Purpose: The purpose of this study was to determine the relationship between primigravida and low birth weight (LBW) in the NICU of Toto Kabila Regional General Hospital in Bone Bolango Regency. Methods: This study design uses a correlational research design, which aims to analyze the relationship between two or more variables without attempting to determine their influence. The sampling technique used in this study is simple random sampling, with a sample size of 113 newborns delivered by cesarean section with a history of primigravida pregnancy in the NICU of Toto Kabila Regional General Hospital. The statistical analysis used is the Kolmogorov-Smirnov test. Results: The results of the study obtained a p-value of 0.273 > 0.05, meaning that there is no relationship between primigravida and the incidence of LBW in the NICU room of Toto Kabila Regional General Hospital, Bone Bolango Regency. Conclusion: It is hoped that this can serve as information and a solution to improve the quality and standard of NICU services in reducing the incidence of LBW. For educational institutions, especially nursing schools, it is hoped that this can provide additional information in developing and conducting further research on factors related to LBW in primigravida, such as maternal health status, factors related to pregnancy outside of marriage, ANC visits, and nutritional status.